Assosiation of maternal factors on stunting incidence in toddlers at Cempaka Inpatient Health Center, Banjarbaru - Octaviani, Indah; Palimbo, Adriana; Suhartati, Susanti; Yuliana, Fitri; Jannah, Raudhatul (Ananda - Health & Education Foundation, 2025)
Background: Stunting is a serious public health issue that affects children's physical and cognitive development, leading to long-term economic consequences. Despite various interventions, stunting prevalence remains high in Indonesia, particularly in areas with limited access to nutrition and healthcare. Maternal factors, including maternal age, nutritional status during pregnancy, and maternal height, are believed to play a crucial role in stunting incidence among children. Objective: This study aims to analyze the relationship between maternal age during pregnancy, nutritional status based on mid-upper arm circumference (MUAC), and maternal height with stunting incidence in toddlers in the working area of Cempaka Inpatient Health Center, Banjarbaru. Method: A case-control study design was employed, involving 212 mothers with toddlers, divided into 106 cases (stunted toddlers) and 106 controls (normal toddlers). Data were collected through structured interviews and anthropometric measurements. The relationship between maternal factors and stunting incidence was analyzed using the Chi-Square test and Odds Ratio (OR) calculations, with a significance level of p<0.05. Results: The findings revealed a significant association between maternal age and stunting incidence, where mothers of high-risk age (<20 years or >35 years) had 2.950 times higher odds of having stunted children (p=0.003). Maternal nutritional status, measured by MUAC <23.5 cm, was also significantly associated with stunting (OR=2.865; p=0.002). Additionally, maternal height <150 cm increased the risk of stunting by 3.143 times compared to mothers with a height ≥150 cm (p=0.001). Conclusion: Maternal factors, including age, nutritional status during pregnancy, and height, significantly contribute to stunting incidence. Strengthening maternal health interventions focusing on adequate nutrition and optimal pregnancy planning is crucial to preventing stunting from an early stage.